Transformative Islamic Da'wah: Back to Local Wisdom Values - Mohammad Isfironi (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2025)
Da'wah in the Post-Truth era uses various internet-based platforms. This offers great opportunities for religious involvement in life, but also presents challenges related to the authenticity, quality of content and commercialization of religion, which has the implication of degrading the critical power of the people. For this reason, da'wah is needed that is centered on da'wah partners by understanding the situation of da'wah partners critically and deeply, then we find methods, media and da'wah actions that suit their needs. Transformative da'wah encourages people to be active in improving their surroundings, overcoming injustice and improving the quality of life through the application of religious values in daily life as local wisdom.